Mycobacterium bovis Cervical Discitis as a Complication of Intravesicular Bacillus Calmette-Guérin Irrigation Treatment. Issue 2 (March 2015) - Dahya, Vishal; Boss, Tove; Robinson, Marjorie; Ramgopal, Moti
<x xml:space="preserve">Abstract</x> Abstract We report a culture-proven case of Mycobacterium bovis cervical osteomyelitis in a 90-year-old man who had undergone intravesical Bacillus Calmette-Guérin (BCG) therapy for bladder cancer 5 months previously. He presented to the emergency department with a worsening discomfort in his neck and had radiographic evidence of discitis and involvement of the adjacent C6 and C7 vertebral bodies. Computed tomography–guided aspiration was performed, and culture of the aspirate confirmed infection with M. bovis. Antituberculous therapy was started at this time, and the patient subsequently responded well clinically. Osteomyelitis is a very rare complication of BCG irrigation treatment and has been known to affect the lumbar and thoracic spine. This is the first ever case reported of cervical discitis from M. bovis after BCG irrigation treatment.